2010
DOI: 10.1029/2010gl045796
|View full text |Cite
|
Sign up to set email alerts
|

The reversal of the rotational modulation rates of the north and south components of Saturn kilometric radiation near equinox

Abstract: It has been known for many years that Saturn emits intense radio emissions at kilometer wavelengths and that this radiation is modulated by the rotation of the planet at a rate that varies slowly on time scales of years. Recently it has been shown that the radio emission consists of two components that have different rotational modulation rates, one emitted from the northern auroral region and the other emitted from the southern auroral region. In this paper we show using radio measurements from the Cassini sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
109
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(122 citation statements)
references
References 22 publications
13
109
0
Order By: Relevance
“…The periods converged during 2009, but so far there is no consensus when the SKR periods crossed or coalesced. Gurnett et al (2010) suggested that the periods coalesced in spring 2010, similar to , who suggested a crossing of two very close periods around the same time in spring 2010. The question is related to the proper identification of northern and southern SKR, where the wave polarization and the spacecraft latitude can be used to separate northern from southern SKR intensities.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…The periods converged during 2009, but so far there is no consensus when the SKR periods crossed or coalesced. Gurnett et al (2010) suggested that the periods coalesced in spring 2010, similar to , who suggested a crossing of two very close periods around the same time in spring 2010. The question is related to the proper identification of northern and southern SKR, where the wave polarization and the spacecraft latitude can be used to separate northern from southern SKR intensities.…”
mentioning
confidence: 64%
“…Fischer et al (2014) suggested that northern and southern periods crossed in late August 2009, just a few weeks after Saturn equinox on 11 August 2009. Nevertheless, all authors (Gurnett et al, 2010;Fischer et al, 2014) agree that northern and southern periods are very similar (∼ 10.7 h) in spring 2010. In contrast to that, the periods of magnetic field oscillations of both hemispheres did not cross in the time interval studied until late 2012 .…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…It is now known that the SKR rotational modulation period is not only variable, but has two periods [Kurth et al, 2008], one at about 10.6 hr that originates primarily from a source in the northern auroral region, and the other at about 10.8 hr that originates primarily from a source in the southern auroral region [Gurnett et al, 2009a]. Recent Cassini data show that these two periods reversed a few months after the August 2009 equinox [Gurnett et al, 2010a;Lamy, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Note the crossing of the first (south) and second (north) SKR component several months after equinox. a series of detailed investigations Gurnett et al, 2010;Lamy, 2011). The most intriguing fact is the appearance of a second component of SKR observed in the northern hemisphere of Saturn with a significantly different rotational periodicity (Fig.…”
Section: Saturn Radio Emission Periodicitymentioning
confidence: 99%